Teaching outbreak investigation to undergraduate food technologists. Issue 2 (2nd February 2015) - Karlsen, Hanne; Mehli, Lisbeth; Wahl, Erik; Staberg, Ragnhild Lyngved
Abstract : Purpose: – Investigations of food-borne outbreaks are complex and require multidisciplinary collaboration. The purpose of this paper is to help food technologists face this challenge and be competent members of a multidisciplinary team, a study module on the investigation of a "real-life" food-borne outbreak was developed. Design/methodology/approach: – The module design was based on the principles of inquiry-based learning with the purpose to motivate and activate students with challenging assignments. The didactic impact of the module was evaluated as a qualitative case study with questionnaires, reflection assignments and interviews of students and lecturers. Findings: – A teaching module developed by an external professional taking part in the academic environment provides a learning environment well adapted to the curriculum, as well as bringing first-hand realism and enthusiasm into the classroom. The external lecturer's dedication to the subject was appreciated by the students. A majority of the students believed that the outbreak investigation simulation play gave a better understanding of how food-borne outbreaks are investigated. A majority of the students 68 per cent (2011) and 82 per cent (2012) believed that what they learned in this module would be useful in a future work situation. Research limitations/implications: – There are some limitations to the study, the most important one being the small sample size, and as the classes rarely exceeds 30 students, the use of a control group was not logistically feasible. Originality/value: – Teaching food technologists to become knowledgeable professionals in this field will constitute a valuable contribution to the multidisciplinary food-borne outbreak investigation team. In turn, this may increase confidence among the general public in the food industry.